Gibbs free energy of formation of Cu2In2O5 ternary phase determined by E.M.F. method (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
Employing electrochemical cells with the solid zirconia electrolyte:Cu2O,CuO /O2- / airCu2In2O5, In2O3,Cu2O / O2-/ airIn,In2O3 /O2-/ Ni, NiOGibbs free energy of formation of solid Cu2In2O5 phase as well as that for In2O3 and CuO oxides was determined in the temperature range from 973 K to 1372 K. The results obtained in this study were used to derive Gibbs free energy change of the reaction of formation of the ternary compound from respective oxides:2CuO + In2O3 = Cu2In2O5which is equal to:  (±1400 J/mol). Oxygen potential diagrams for the Cu–In–O system are also given at two temperatures.
Keywords: E.M.F. method; Gibbs free energy; Formation of Cu2In2O5